Water and Radiation Use Efficiencies in Sorghum. (1st May 2013) - Narayanan, Sruthi; Aiken, Robert M.; Vara Prasad, P. V.; Xin, Zhanguo; Yu, Jianming
Abstract : Increasing water and radiation use efficiencies (WUE and RUE, respectively) are critical to enhance crop production. Exploring genetic variability in WUE and RUE is necessary to improve these traits. The objectives of this research were to evaluate eight sorghum [ Sorghum bicolor (L.) Moench] genotypes for biomass production, WUE, and RUE and to test whether the differences in WUE among sorghum genotypes were associated with increased biomass production or decreased water use under field conditions. The WUE was estimated as the slope of the regression of aboveground biomass on cumulative water use for specified sampling intervals. The RUE was estimated as the slope of the regression of aboveground biomass on cumulative intercepted photosynthetically active radiation (IPAR). Sorghum genotypes showed significant differences in biomass production, WUE, and RUE. The WUE varied from 3.39 ± 0.80 to 5.42 ± 0.80 g kg −1 in 2009 and from 4.04 ± 0.58 to 7.63 ± 0.58 g kg −1 in 2010. Similarly, RUE varied from 2.13 ± 0.33 to 3.53 ± 0.31 g MJ −1 IPAR in 2009 and from 2.08 ± 0.35 to 3.83 ± 0.33 g MJ −1 IPAR in 2010. Among the eight sorghum genotypes tested in this study, IS 27111 and IS 27150 had the largest biomass production, WUE, and RUE. The WUE was more strongly correlated to biomass production than to water use. This result implies that it is possible to improve WUE without compromising biomass production. The sorghum genotypes evaluated for biomass production, WUE, and RUE in this study offer useful plant materials for identifying the mechanisms causing differences in these traits.